The Correlation between Spiritual Health and Maternal-Fetal Attachment Behaviors in Pregnant Women Referring to the Health Centers in Qazvin, Iran - Shahnaz Tork Zahrani; Elnaz Haji Rafiei; Sepideh Hajian; Hamid Alavi Majd; Ahmad Izadi (Shiraz University of Medical Sciences, 2020)
Background: Spiritual health and maternal-fetal attachment behaviors are considered as beneficial coping strategies used to adapt to pregnancy. The present study was conducted to determine the correlation between spiritual health and maternal-fetal attachment behaviors in pregnant women referring to health centers in Qazvin. Methods: The present descriptive correlational study was conducted on 200 pregnant women referring to health centers in Qazvin, in 2015. A multi-stage sampling was carried out and data were collected in a self-report manner, using the Persian version of Spiritual Well-Being scale developed by Paloutzian and Ellison, Persian version of Cranley's maternal-fetal attachment scale, and a demographic and midwifery questionnaire. Data were analyzed in SPSS-20, using Pearson's correlation coefficient and the multivariate linear regression. PResults: The mean scores of attachment and spiritual health were 95.91±8.92 and 104.15±10.59, respectively. A weak positive correlation was observed between attachment behaviors and spiritual health (P<0.001, r=0.40). Regression analysis showed that spiritual health (P<0.001, β=0.40), religious health (P<0.001, β=0.30), and existential health (P<0.001, β=0.43) could predict the maternal-fetal attachment behaviors. Conclusion: The results showed that a higher spiritual health was associated with an increase in maternal-fetal attachment behaviors. These results suggest the importance of strengthening spirituality during pregnancy as an effective strategy for increasing the attachment behaviors.